Preliminary definition of CORTEX system architecture - Brudna, C. (2009)
The objective of D4 is to present a preliminary definition of the CORTEX system architecture. Given the early progress stage of work package 3, and being this a deliverable comprising preliminary results, it mainly focus on the components that are necessary to implement the communication abstractions developed in WP2, that is, the work developed under task 3.1. Following the WAN-of-CAN structure envisaged in CORTEX, the work presented in deliverable D4 includes a preliminary definition of a prototype of a WAN-of-CAN structure based on CAN-bus for the CAN level and on a TCP/IP network for the WAN level. It addresses some important aspects related with predictability of message transfer and ordering of messages. Furthermore, D4 also focusses on wireless infrastructures as a key technology to implement many of the properties of applications foreseen in CORTEX, namely by proposing a new protocol, named TBMAC (for Time-Bounded Medium Access Control), which provides mobile hosts with predictable access to the wireless medium. Finally, D4 also describes the Timely Computing Base, which can be seen as a special architectural component serving the whole system and providing crucial time related services. This TCB component will play an important role in the definition of the communication services and protocols, scheduled as task 3.2. The work presented in deliverable D4 will serve as a basis for successor deliverables (D5 and D7) and will be consolidated towards the end of the project, in deliverable D11